ANALYSIS OF LDL-C MEASUREMENT USING DIRECT AND FRIEDEWALD FORMULA IN TYPE 2 DIABETES MELLITUS PATIENTS - Liong Boy Kurniawan; Windarwati Windarwati; Budi Mulyono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
LDL-C is important to evaluate the risk of cardiovascular disease. LDL-C can be measured directly or by using the Friedewald equation. Type 2 Diabetes Mellitus (DM) patients have tighter LDL-C target compared with normal population. This research is aimed to analyze the difference of LDL-C level measured by direct test and Friedewald equation in DM and non-DM. This research was a cross-sectional study using LDL-C data of 208 patients who were tested in Laboratory of Clinical Pathology, Hasanuddin University Hospital from a period of August 2015 to January 2016. LDL-C and other lipid were measured using ABX Pentra 400 meanwhile Friedewald LDL-C was calculated with equation LDLC= Total Cholesterol-HDL-C-(1/5 Triglycerides). Type 2 DM patients were diagnosed by ADA 2015 criteria or who had previous DM history. Friedewald LDL-C estimates lower than direct method (139.07+50.60 mg/dL vs 155.33+51.74 mg/dL, p=0.000). Delta of direct LDL-C and Friedewald equation measurement is higher in DM than non-DM patients (11.97+11.52% vs 8.49+11.27%, p=0.030) Fridewald LDL-C estimates LDL-C lower than direct method and the difference is wider in DM than non-DM. It is suggested to measure LDL-C directly in DM type 2 to reach the actual LDL-C target.